Average
MCQs Math


Question:     Find the average of odd numbers from 11 to 653


Correct Answer  332

Solution And Explanation

Solution

Method (1) to find the average of the odd numbers from 11 to 653

Shortcut Trick to find the average of the given continuous odd numbers

The odd numbers from 11 to 653 are

11, 13, 15, . . . . 653

After observing the above list of the odd numbers from 11 to 653 we find that the difference between two consecutive terms are equal. This means the list of the odd numbers from 11 to 653 form an Arithmetic Series.

In the Arithmetic Series of the odd numbers from 11 to 653

The First Term (a) = 11

The Common Difference (d) = 2

And the last term (ℓ) = 653

The average of the numbers forming an Arithmetic Series

= The first term (a) + The last term (ℓ)/2

⇒ The average of numbers forming an Arithmetic Series = a + ℓ/2

Thus, the average of the odd numbers from 11 to 653

= 11 + 653/2

= 664/2 = 332

Thus, the average of the odd numbers from 11 to 653 = 332 Answer

Method (2) to find the average of the odd numbers from 11 to 653

Finding the average of given continuous odd numbers after finding their sum

The odd numbers from 11 to 653 are

11, 13, 15, . . . . 653

The odd numbers from 11 to 653 form an Arithmetic Series in which

The First Term (a) = 11

The Common Difference (d) = 2

And the last term (ℓ) = 653

The Average of the given numbers

= Sum of the given numbers/Total number of given numbers

Thus, to find the average of the given numbers, first, we need to find their sum and the total number of given numbers

Finding the number of terms

For an Arithmetic Series, the nth term

an = a + (n – 1) d

Where

a = First term

d = Common difference

n = number of terms

an = nth term

Thus, for the given series of the odd numbers from 11 to 653

653 = 11 + (n – 1) × 2

⇒ 653 = 11 + 2 n – 2

⇒ 653 = 11 – 2 + 2 n

⇒ 653 = 9 + 2 n

After transposing 9 to LHS

⇒ 653 – 9 = 2 n

⇒ 644 = 2 n

After rearranging the above expression

⇒ 2 n = 644

After transposing 2 to RHS

⇒ n = 644/2

⇒ n = 322

Thus, the number of terms of odd numbers from 11 to 653 = 322

This means 653 is the 322th term.

Finding the sum of the given odd numbers from 11 to 653

The sum of all terms (S) in an Arithmetic Series

= n/2 (a + ℓ)

Where, n = number of terms

a = First term

And, ℓ = Last term

Thus, the sum of all terms (S) of the given odd numbers from 11 to 653

= 322/2 (11 + 653)

= 322/2 × 664

= 322 × 664/2

= 213808/2 = 106904

Thus, the sum of all terms of the given odd numbers from 11 to 653 = 106904

And, the total number of terms = 322

Since, the average of the given numbers

= Sum of the given numbers/Total number of given numbers

Thus, the average of the given odd numbers from 11 to 653

= 106904/322 = 332

Thus, the average of the given odd numbers from 11 to 653 = 332 Answer


Similar Questions

(1) Find the average of even numbers from 4 to 1004

(2) Find the average of odd numbers from 11 to 145

(3) Find the average of the first 506 odd numbers.

(4) Find the average of even numbers from 6 to 810

(5) Find the average of even numbers from 10 to 1946

(6) Find the average of the first 1964 odd numbers.

(7) Find the average of even numbers from 4 to 302

(8) Find the average of odd numbers from 9 to 703

(9) Find the average of the first 2318 odd numbers.

(10) Find the average of even numbers from 10 to 1512


NCERT Solution and CBSE Notes for class twelve, eleventh, tenth, ninth, seventh, sixth, fifth, fourth and General Math for competitive Exams. ©